Replicability of Physical Exercise Interventions in Lung Transplant Recipients; A Systematic Review - Knols, Ruud H.; Fischer, Nicolas; Kohlbrenner, Dario; Manettas, Anastasios; de Bruin, Eling D. (Frontiers in Physiology, 2018)
Introduction This systematic review aimed to assess the replicability of physical exercise interventions in lung transplantation patients. For replicability we focused on (1) the description of training principles, (2) the description of FITT components and adherence to the interventions, (3) the amount of detailed information given on the physical exercise intervention, and (4) reporting the methodological quality of the included works. Methods Relevant databases (Medline-Ovid, EMBASE, CINAHL, PsychInfo, Cochrane Library) were searched. Author dyads selected and systematically analysed the included studies independent from each other. A purpose developed checklist was used to assess the details of the exercise interventions and their methodological quality. Results From the seven included manuscripts, three described resistance training, one endurance, and three combined training approaches. All manuscripts reported specificity and initial values, six manuscripts mention85% progression and overload. The exercise principle reversibility was reported once and diminishing returns was not reported at all. All studies reported the type of exercise, three studies reported intensity and one study reported time for training. Not any study completely reported frequency or described adherence to the intervention. Lack of detailed reporting was identified as the cause for murky description of the interventions. The highest score for intervention description was 5 of possible 12 items. Conclusions This review showed that rReplicability of many exercise interventions in LTX is not warranted due too poor descriptions of important items related to training. In particular there were insufficiently detailed reporting of training principles and FITT components in programs developed for LTX. Future interventions that aim to train LTX patients should spent effort in writing reports in which the intervention is detailed to such an extent that full replicability in clinical settings can be guaranteed.